Ochratoxin A activates opposing c-MET/PI3K/Akt and MAPK/ERK 1-2 pathways in human proximal tubule HK-2 cells - Ozcan, Zeynep; Gul, Gizem; Yaman, Ibrahim (Springer Heidelberg, 2015)
Ochratoxin A (OTA) is a mycotoxin produced as a secondary metabolite by filamentous fungi, such as Aspergillus and Penicillium. Because OTA is a common contaminant of food and feeds, humans and animals are frequently exposed to OTA in daily life. It has been classified as a carcinogen in rodents and a possible carcinogen in humans. OTA has been shown to deregulate a variety of different signal transduction pathways in a cell type- and dosage-depending manner resulting in contrasting physiological effects, such as survival or cell death. While the ERK1-2 and JNK/SAPK MAPK pathways are major targets, knowledge about their role in OTA-mediated cell survival and death is fragmented. Similarly, the contribution of the PI3K/Akt pathway to the carcinogenic effect of OTA in proximal tubule cells has not been elucidated in detail. In this study, we demonstrated that OTA induced sustained activation of the PI3K/Akt and MEK/ERK1-2 signaling pathways in a dose- and time-dependent manner in HK-2 cells. Chemical inhibition of ERK1-2 activation or overexpression of dominant-negative and kinase-dead MEK1 leads to increased cell viability and decreased apoptosis in OTA-treated cells. Blockage of PI3K/Akt with Wortmannin aggravated the negative effect of OTA on cell viability and increased the levels of apoptosis. Moreover, we identified the c-MET proto-oncogene as an upstream receptor tyrosine kinase responsible for OTA-induced activation of PI3K/Akt signaling in HK-2 cells. Our data suggest that OTA may potentiate carcinogenesis by sustained activation of c-MET/PI3K/Akt signaling through suppression of apoptosis induced by MEK/ERK1-2 activation in damaged renal proximal tubule epithelial cells.
Keywords: Ochratoxin A; ERK1-2; Akt; c-MET; Apoptosis; HK-2 cells